2019
DOI: 10.1123/ijsnem.2018-0135
|View full text |Cite
|
Sign up to set email alerts
|

Social Media as a Nutrition Resource for Athletes: A Cross-Sectional Survey

Abstract: Social media contains a wealth of nutrition information and proposes a cost-effective, highly engaging platform to deliver nutrition information to athletes. This study used an online questionnaire to determine whether New Zealand athletes are using social media as a source of nutrition information and to understand perceptions of social media as a nutrition resource. Quantitative data were analyzed using t tests, chi-squared tests, and logistic regression analysis. Inductive thematic analysis was adopted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Teammates and family members who have not received appropriate training can provide incorrect and potentially harmful information. Additionally, it is important that athletes are aware of the possibility of unreliable information being presented through digital channels (24).…”
Section: Post-lockdownmentioning
confidence: 99%
“…Teammates and family members who have not received appropriate training can provide incorrect and potentially harmful information. Additionally, it is important that athletes are aware of the possibility of unreliable information being presented through digital channels (24).…”
Section: Post-lockdownmentioning
confidence: 99%
“…Others have documented this discrepancy (Moorhead et al, 2013;Oh & Kim, 2014) between high utilization and low trustworthiness for health and nutrition information on social media. Bourke et al (2019) report that athletes use this source because it is ''convenient, free and fast,'' noting that information often ''pops up'' during social media use without having to look for it. Given the demonstrated interest in scientific information, it may be beneficial for researchers and dietitians to utilize this source as an effective means of directly communicating with athletes.…”
Section: Use Of Social Mediamentioning
confidence: 99%
“…The results of this study did not indicate that the use of social media in the introductory nutrition course was of value when modifying a college student's readiness to change regarding nutritional lifestyle behaviors and there were only significant alterations in dietary intake relating to dairy and protein foods (Crawford-Ciglar, 2017) As far as athletes and their use of social media as a resource, 306 New Zealand athletes were surveyed to determine whether they are using social media as a source of nutrition information and to understand perceptions of social media as a nutrition resource. Of the athletes surveyed, 65% reported using social media for nutrition purposes in the past 12 months (Bourke et al, 2019). It was found that female athletes were more likely to use social media for nutrition purposes than males and elite athletes were less likely to use social media for nutrition purposes compared to recreational athletes.…”
Section: Education Via Social Mediamentioning
confidence: 97%
“…There is also very limited research that has been done to examine how social media is used in the sports nutrition world. From the research that has been done, it has been found that female athletes are more likely to use social media for nutrition purposes and athletes commonly used social media for practical nutrition purposes related to recipes or information about restaurants (Bourke et al, 2019). Sports nutritionists have been encouraged to embrace social media and to utilize it for interventions to their athletes (Dunne et al, 2019).…”
Section: Protein Knowledge Related To Year In School and Sportmentioning
confidence: 99%
See 1 more Smart Citation